2018
DOI: 10.2337/db17-0316
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Mitochondria-Associated Endoplasmic Reticulum Membrane (MAM) Integrity Contributes to Muscle Insulin Resistance in Mice and Humans

Abstract: Modifications of the interactions between endoplasmic reticulum (ER) and mitochondria, defined as mitochondria-associated membranes (MAMs), were recently shown to be involved in the control of hepatic insulin action and glucose homeostasis, but with conflicting results. Whereas skeletal muscle is the primary site of insulin-mediated glucose uptake and the main target for alterations in insulin-resistant states, the relevance of MAM integrity in muscle insulin resistance is unknown. Deciphering the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
183
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(193 citation statements)
references
References 46 publications
9
183
1
Order By: Relevance
“…Mfn2 or Grp75 overexpression reversed the effects of palmitate on MAM proteins and on insulin signaling . Moreover, myotubes from obese patients and from obese patients with type 2 diabetes showed decreased mitochondria–ER contacts compared to those of healthy patients . In contrast to these results, Arruda et al found an increase in the MAM proteins MCU and RyR in soleus muscles from ob/ob and HFD‐fed mice, suggesting an enrichment in MAMs under these conditions.…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 93%
See 1 more Smart Citation
“…Mfn2 or Grp75 overexpression reversed the effects of palmitate on MAM proteins and on insulin signaling . Moreover, myotubes from obese patients and from obese patients with type 2 diabetes showed decreased mitochondria–ER contacts compared to those of healthy patients . In contrast to these results, Arruda et al found an increase in the MAM proteins MCU and RyR in soleus muscles from ob/ob and HFD‐fed mice, suggesting an enrichment in MAMs under these conditions.…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 93%
“…Ablation of GRP75 , the bridge between IP3R and VDAC, has been reported to cause a r eduction in VDAC1/IP3R1 interactions in human liver cells and in myotubes . Moreover, GRP75 deficiency reduces insulin signaling and insulin action in HuH7 liver cells (Fig A). The depletion of GRP75 in medullary thyroid carcinoma cells induces the MEK/ERK pathway and increases oxidative stress .…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 94%
“…For example, in liver, obesity leads to a marked enhancement of MAM that alters interorganellar calcium dynamics and causes increased oxidative stress and metabolic derangement [14]. MAM disruption and miscommunication have also been implicated in muscle insulin resistance in mice and humans [15], and hepatic insulin resistance [16], respectively. Intriguingly, MAM is thought to be the site of isolation membrane for the formation of selective autophagosomes for mitochondria [17].…”
Section: Er Interconnections With Other Organellesmentioning
confidence: 99%
“…Skeletal muscle is the primary site of insulin-mediated glucose uptake and is the main organ affected by insulin resistance and diabetes. Palmitate disrupts normal insulin signaling and alters insulin sensitivity in skeletal muscle and MAM disorganization has been involved in the mechanism [15]. However, concomitant exposure to oleate abolishes ER stress in human myotubes [89].…”
Section: Insulin Receptor Modulationmentioning
confidence: 99%
“…40 Abnormal MAM functions also are known to cause type 2 diabetes. 48,49 This evidence suggests that MAMs are likely a key signaling hub. Although no direct associations between kidney disease and MAMs have been reported to date, considering their function, malfunctioning MAMs potentially could cause kidney diseases.…”
mentioning
confidence: 97%